Analisis Kelayakan Finansial Usahatani Melon di PT. Tobo Agriculture Group Kota Bengkulu - Erika Nanda Sasmita; Ana Nurmalia; Yossie Yumiarti (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
PT. Tobo Agriculture Group Bengkulu City, located in Jenggalu Subdistrict, Bengkulu City, is a business engaged in hydroponic melon cultivation. The objectives of this study are (1) to analyze the financials of melon farming at PT. Tobo Agriculture Group Bengkulu City, (2) to analyze the feasibility of melon farming at PT. Tobo Agriculture Group Bengkulu City. The research method used is a quantitative method with financial and farm feasibility analysis. The interest rate used is 10% based on the average commercial bank interest rate in 2022–2024. The results showed that revenue increased from Rp231.480.000 in 2022 to Rp502.882.000 in 2024 with an average income of Rp152.744.369. The results indicate that melon farming is financially feasible and has the potential to be developed. Based on: (a) the obtained R/C Ratio value of 1.88. (b) NPV value of Rp381,824,335.49 (>0). (c) IRR of 72.82%. (d) Gross B/C of 1.93 (>1). (e) PBP value of 2 months 22 days indicates relatively quick capital recovery.